The perception of Islamic hire purchase facility: a case study among staff in Jabatan Pelajaran Negeri Kelantan / Noradilah Mustapa - Mustapa, Noradilah (Faculty of Business and Management, 2013)
The purpose of this study is to investigate the level of perception on Islamic hire purchase facility (AITAB) among staffs in Jabatan Pelajaran Negeri Kelantan. This study analyzes and identifies the level and also the relationship between perception of Islamic hire purchase facility (AITAB) and features product, quality service and knowledge among staff in JPN Kelantan. The three research questions addressed are: What the level of staff perception toward Islamic Hire Purchase Facility (AITAB)? What the level all the independent variables which are features product, quality service and knowledge toward Islamic hire purchase facility (AITAB)? And is there any significant relationship between perception of Islamic hire purchase facility (AITAB) and features product, quality service and knowledge? A survey method was used a sample of 60 respondents in ten departments at Jabatan Pelajaran Negeri Kelantan. The theoretical framework is modified from Nurdianawati Irwani et al (2006). The study also develops Normality Test, Reliability Test, Frequency Analysis and Pearson Correlation. The finding of the study revealed that the level of perception and relationship between dependent and independent variables. The result found that the level perception toward Islamic hire purchase facility (AITAB) among staff in JPN Kelantan almost agree and significant relationship with all variables which are perception of Islamic hire purchase facility (AITAB), features product, quality service and knowledge. This research also mentioned the recommendations and suggestion for future research. For the perception and features product, researcher suggests providing Islamic hire purchase facility (AITAB) information. For the quality service among bank officer and car dealer, manager also should training the staff and car dealers also must have knowledge of Islamic financial product. For the knowledge, bank and other financial institution should make more campaign and promotion for public to obtain the correction information about the product.